2012
DOI: 10.1080/15374416.2012.703123
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Vulnerabilities and Depression Versus Other Psychopathology Symptoms and Diagnoses in Early Adolescence

Abstract: Objective We examined the concurrent associations between multiple cognitive vulnerabilities to depression featured in Hopelessness Theory, Beck’s Theory, and Response Styles Theory and depressive symptoms and diagnoses in a sample of early adolescents. We also examined the specificity of these cognitive vulnerabilities to depression versus anxiety and externalizing psychopathology, controlling for co-occurring symptoms and diagnoses. Method Male and female, Caucasian and African-American, 12–13 year old ado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
114
1
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 117 publications
(122 citation statements)
references
References 92 publications
(128 reference statements)
3
114
1
3
Order By: Relevance
“…The relationship between positive processing and depression was consistent with previous studies (2012; Gençöz et al, 2001; Hammen & Zupan, 1984; Hayden, Olino, Mackrell, et al, 2013; Prieto et al, 1992; Timbremont & Braet, 2004; Zupan, Hammen, & Jaenicke, 1987). However, the literature on negative processing and depression in youth is less consistent, with some studies (Prieto et al, 1992; Timbremont & Braet, 2004; Zupan, Hammen, & Jaenicke, 1987), but not others (e.g., Alloy et al, 2012; Black & Pössel, 2013; Gençöz et al, 2001; Hammen & Zupan, 1984) reporting a significant association. In some cases, non-significant findings may be due to sample sizes too small to detect small-to-medium effects and to methodological differences, such as the lack of a sad mood induction prior to the SRET, which is important for detecting associations between SRET performance and depressive vulnerabilities (Evraire et al, in press).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The relationship between positive processing and depression was consistent with previous studies (2012; Gençöz et al, 2001; Hammen & Zupan, 1984; Hayden, Olino, Mackrell, et al, 2013; Prieto et al, 1992; Timbremont & Braet, 2004; Zupan, Hammen, & Jaenicke, 1987). However, the literature on negative processing and depression in youth is less consistent, with some studies (Prieto et al, 1992; Timbremont & Braet, 2004; Zupan, Hammen, & Jaenicke, 1987), but not others (e.g., Alloy et al, 2012; Black & Pössel, 2013; Gençöz et al, 2001; Hammen & Zupan, 1984) reporting a significant association. In some cases, non-significant findings may be due to sample sizes too small to detect small-to-medium effects and to methodological differences, such as the lack of a sad mood induction prior to the SRET, which is important for detecting associations between SRET performance and depressive vulnerabilities (Evraire et al, in press).…”
Section: Discussionmentioning
confidence: 96%
“…Derry & Kuiper, 1981) or by the total number of endorsed words (e.g. Prieto, Cole, & Tageson, 1992), but a number of other approaches have also been used (e.g., Alloy et al, 2012; Gençöz, Voelz, Gençöz, Pettit, & Joiner, 2001). In the present review, we consider studies of youth that included some measure of adjective recall, regardless of how the recall measure was calculated.…”
mentioning
confidence: 99%
“…To be eligible for participation in the study, adolescents had to be 12 or 13 years old, self-identify as Black/African-American or White/Caucasian, and have a mother or primary female caregiver who was also willing to participate in the study 1 . Exclusionary criteria included: 1) the absence of a mother or female caregiver, 2) the adolescent or mother was mentally retarded, psychotic, or had a severe developmental disorder or severe learning disability, and 3) the inability to complete measures in the study by adolescents or mothers due to being unable to speak or read English (for more details regarding recruitment, see Alloy et al, 2012). …”
Section: Methodsmentioning
confidence: 99%
“…The measure may be divided into 4 subscales: physical symptoms, social anxiety, separation anxiety/panic, and harm avoidance; however, in the present study only the total score was utilized (range = 0 – 117). Past research has found the MASC to be a reliable and valid tool for measuring symptoms of youth anxiety (Alloy et al, 2012; Brozina & Abela, 2006). Cronbach’s alphas ranging between 0.88 and 0.90 across administrations were found in the present study.…”
Section: Methodsmentioning
confidence: 99%